Comparative labour law and industrial relations in industrialized market economies. XIth Ed. (The Hague, 2014)
"Comparativism is no longer a purely academic exercise but has increasingly become an urgent necessity for industrial relations and legal practitioners due to the growth of multinational enterprises and the impact of international and regional organizations aspiring to harmonize rules. The growing need for comprehensive, up-to-date and readily available information on labour law and industrial relations in different countries led to the publication of the International Encyclopaedia for Labour Law and Industrial Relations, in which more than 70 international and national monographs have thus far been published.